Detection of The Existence of Viral Nervous Necrosis on Fry Cantang Grouper at Rain Season - Wahyu Nurlita; I Gde Suranaya Pandit; Ni Made Darmadi (SEAS (Sustainable Environment Agricultural Science), 2020)
Viral Nervous Necrosis (VNN) disease is one of the major causes of failure in grouper aquaculture activities. The pathogens attack the central nervous system, eyes retina, and reproductive organs. When the rainy season starts, it may generate lower water quality for aquaculture, which becomes a suitable condition for VNN infections in fry cantang grouper. For this reason, there is an emerged need to do the detection of the existence of Viral Nervous Necrosis (VNN) pathogen fry cantang grouper cultured at the rain season. Data analysis was carried out in descriptive ways that aim to make data are presented by the actual situation without giving any treatment so that it can be easily discussed with existing theory to conclude. The examination on the presence of Viral Nervous Necrosis (VNN) disease on fry cantang grouper lived at rain season was conducted using two methods which are conventional PCR and Real-time PCR. From 20 samples of fry cantang grouper taken for this study, 5 samples were detected positive Viral Nervous Necrosis (VNN) its equal to the prevalence of 25%. Histopathological observation on fry cantang grouper infected Viral Nervous Necrosis (VNN) show the appearance of vacuoles on ganglion cell layer, inner nuclear layer, and pigment epitel, a sign of lysis on the liver, vacuoles on the brain, necrosa, and hypertrophy on the brain, and the appearances of melano macrophage center on the kidney. The average water quality in the pond was reported at the temperature of 29.2 0C, salinity 33 ppt, and pH 8.3